The Role of Social Support as A Moderator in the Relationship between Resilience and PTSD in Individuals Who are COVID-19 Survivors Who Have Comorbidities - Dzahabiya, Farras Aisha; Roswiyani, Roswiyani; Sahrani, Riana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The COVID-19 pandemic has an impact on individual health conditions, especially COVID-19 survivors who have comorbidities. Therefore, to reduce PTSD experienced by COVID-19 survivors, resilience and social support are needed. This study aims to determine the role of social support as a moderator in the relationship between resilience and PTSD in COVID-19 survivors who have comorbidities. Participants in this study were 105 people aged 20-60 years, women and men with comorbid diseases who had been contaminated with the COVID-19 virus. By using quantitative research methods, this research uses the Connor-Davidson Resilience Scale (CD-RISC-25) measuring instrument to measure resilience, the Post Traumatic Stress Disorder Checklist DSM-5 (PCL-5) measuring instrument to measure PTSD, and the Multidimensional Scale Perceived of Social Support (MSPSS) to measure social support. Data analysis using MRA showed that social support did not act as a moderator in the relationship between resilience and PTSD but had a significant direct effect on PTSD.